Effects of Family Structure and Parental Conflict on Adolescent Behavioral Adjustment in Some Selected Universities in Bamenda North West Region of Cameroon - Mirabelle, Yimeli Lonpa (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
Adolescence represents a pivotal stage of development characterized by heightened sensitivity to family dynamics, emotional experiences, and behavioral regulation. Family structure and parental conflict are increasingly recognized as critical determinants of adolescents’ psychosocial functioning, particularly within academic environments. This study, entitled “Effects of Family Structure and Parental Conflict on Adolescents’ Behavioral Adjustment in Some Selected Universities in Bamenda, North West Region of Cameroon,” investigates the extent to which variations in family structure and parental conflict influence the behavioral adjustment of adolescents in higher education. Drawing on ecological systems theory of Bronfenbrenner, attachment theory of Bowlby, and family systems theory of Minuchin, the study provides a multidimensional understanding of how family contexts shape adolescent behavior. A mixed methods research design was adopted, integrating quantitative and qualitative approaches to ensure a comprehensive analysis. The study population comprised undergraduate students, university administrators, and lecturers from selected faculties. A sample of 412 participants was used involving 360 students, 42 administrators, and 10 lecturers. Quantitative data were collected through structured questionnaires administered to students, while qualitative data were obtained through semi-structured interviews with administrators and focus group discussions with lecturers. This triangulation allowed for a nuanced exploration of both statistical trends and lived experiences. Quantitative data were analyzed using descriptive statistics such as frequencies, percentages, means, and standard deviations while inferential statistics included one-way ANOVA, Pearson’s correlation, and multiple regression analysis. Qualitative data were transcribed verbatim, coded, and thematically analyzed to highlight perceptions, narratives, and institutional insights on family-related behavioral issues. For descriptive results, students reported moderate levels of parental conflict (M = 3.32, SD = 0.87) on a 5-point scale, and behavioral adjustment scores indicated moderate levels of externalizing and internalizing symptoms (M = 2.98, SD = 0.81). Family structure was categorized as nuclear (50%), single-parent (27%), and separated/divorced (23%). Frequency analyses revealed that 61% of students from single-parent or separated/divorced families reported occasional or frequent difficulties with emotional regulation, peer interaction, or classroom engagement. For bivariate relationships, a significant negative correlation was observed between parental conflict and behavioral adjustment (r = -0.48, p < .001), indicating that higher parental conflict was associated with poorer behavioral outcomes. Family structure was also significantly related to behavioral adjustment, with students from separated or divorced families showing higher maladjustment scores (M = 3.41, SD = 0.72) compared to those from nuclear families (M = 2.74, SD = 0.78); ANOVA: F (2,357) = 29.6, p < .001. Multiple regression analysis predicting behavioral adjustment from family structure and parental conflict (controlling for age, gender, and socioeconomic background) yielded a significant model (R² = .35, F (5,354) = 37.8, p < .001). Parental conflict emerged as the strongest predictor (β = -0.44, p < .001), followed by family structure (β = 0.26, p = .003). Mediation analysis further showed that parental conflict partially mediated the relationship between non-nuclear family structures and maladjustment (indirect effect = 0.14, 95% CI [0.07, 0.23]), accounting for 39% of the total effect. Thematic analysis of qualitative interviews and FGDs revealed four dominant themes which are Emotional instability and academic disengagement, administrators reported higher rates of absenteeism, low motivation, and conduct issues among students experiencing high parental conflict. Role modeling and attachment disruptions, lecturers observed that adolescents from non-nuclear families often lacked stable emotional anchors. Institutional support gaps, administrators acknowledged limited psychosocial support services for students facing family-related stress. For resilience and coping, some students displayed adaptive coping mechanisms, facilitated by peer support groups and mentorship programs. Findings indicate that family structure and parental conflict significantly shape adolescents’ behavioral adjustment, with higher conflict and non-nuclear structures associated with increased emotional and behavioral challenges. However, protective factors such as supportive peers, mentors, and university counseling structures can mitigate some of these adverse effects. This study contributes to the growing body of research on adolescent development within African university contexts by emphasizing the powerful influence of family dynamics on behavior. The results underscore the need for universities to implement structured psychosocial support programs, peer mentorship initiatives, and family-oriented counseling services. A holistic and ecological approach involving students, families, educators, and policymakers is essential to fostering healthier behavioral adjustment among adolescents. The findings have strong implications for mental health programming, university guidance services, and policy reforms targeting youth well-being in Cameroon and similar contexts